Synthesis of a Novel 1D/2D Bi2O2CO3–BiOI Heterostructure and Its Enhanced Photocatalytic Activity - Yin Peng (MDPI AG, 2021)
A novel 1D/2D Bi2O2CO3–BiOI heterojunction photocatalyst with high-quality interfaces was synthesized through a hydrothermal method by using Bi2O2CO3 nanorods and KI as raw materials. Two-dimensional (2D) BiOI nanosheets uniformly and vertically grow on the 1D porous Bi2O2CO3 rods. Bi2O2CO3–BiOI heterojunctions exhibit better photocatalytic activity than pure Bi2O2CO3 nanorods and BiOI nanosheets. Cr(VI) (30 mg/L), MO (20 mg/L) and BPA (20 mg/L) can be completely degraded in 8–15 min. The superior photocatalytic performance of 1D/2D Bi2O2CO3–BiOI heterojunction is ascribed to the synergistic effects: (a) vertical 2D on 1D multidimensional structure; (b) the formation of the Bi2O2CO3–BiOI p–n heterojunction; (c) high-quality interfaces between Bi2O2CO3 and BiOI.